Morphological profile of federated weightlifters from the Valparaiso region, Chile - Fuentes-Barría, Héctor; Urbano-Cerda, Sebastián; Aguilera-Eguía, Raúl; González-Wong, Catalina; Vera-Aguirre, Valentina (Universidad y Salud, 2021)
Introduction: Anthropometric profiles allow better planning and execution of sports training in weightlifting. Objective: To describe and compare, according to gender, the anthropometric profile and somatotype of federated weightlifters from the Valparaiso region of Chile. Materials and methods: A descriptive cross-sectional study that included 40 adult weightlifters. The anthropometric assessment was carried out using the measurement and marking protocol of the International Society for Advances in Kinanthropometry, Ross and Kerr pentacompartmental method, and Heath-Carter somatotype. A Student’s t test was applied for independent samples and U Mann-Whitney was used to compare anthropometric characteristics between groups. The statistical power and effect size were calculated using Cohen’s “d”. Results: There are significant differences between groups for: relative (p=0.003; d=0.96) and absolute (p≤0.001; d=2.42) muscle mass; relative fat mass (p≤0.001; d=1.46); absolute bone mass (p≤0.001; d=1.41); relative (p≤0.001; d=1.96) and absolute (p≤0.001; d=0.97) skin mass; relative (p=0.006; d=1.08) and absolute (p≤0.001; d=2.09) residual mass. Based on the somatotype distribution, the male and female groups were classified as Endo-Mesomorph and Mesomorph-Endomorph, respectively, which showed significant differences in mesomorphism (p≤0.001; d=1.48). Conclusions: There is a predominance of the mesomorphic somatotype, with significant differences in the components of the body composition.